Justice perceptions of occupational training subsidies: findings from a factorial survey - Richard Wolff; Olaf Struck; Christopher Osiander; Monika Senghaas; Gesine Stephan (Journal for Labour Market Research, 2022)
Workers whose jobs are affected by structural change and digitization are required to continuously adapt their vocational skills to the requirements of the labor market. This adaptation is also essential for the competitiveness of their employer firms. The German legislature addressed this issue with investive measures for unemployment insurance, one of which is the Qualification Opportunities Act (Qualifizierungschancengesetz). Funds taken from unemployment insurance can now be used to provide financial help for employers in a more direct way and on a broader scale than before. It became possible that not only unemployed individuals but also workers in companies receive state assistance. This paper analyses the extent to which citizens accept such public support programs for further training and which principles of justice they apply when assessing a just amount of training subsidies. We conducted two factorial surveys. First, we investigated the justice assessments of training subsidies for different types of firms. The results showed that citizens are inclined to subsidize companies by receiving social security funds for further training of their employees. However, when doing so, the principle of needs-based justice should be complied with. Second, we analyze whether citizens think it is just or unjust to provide training subsidies to different workers, as we present them with changing characteristics of workers. The findings confirmed that in addition to the principle of need, views on performance justice, as well as economic considerations are relevant in assessments of whether training subsidies co-financed by unemployment insurance are just.
Keywords: C99; D63; I38; J08; J24; J65; 330; Factorial survey; Justice assessments; Multilevel and mixed effects model; Occupational training; Unemployment insurance